Ivermectin mass drug administration to humans for malaria parasite transmission control - Kobylinski, Kevin, author; Foy, Brian D., advisor; Eisen, Lars, committee member; Huyvaert, Kathryn P., committee member; Rosenberg, Ronald, committee member (Colorado State University. Libraries, 2011)
Every year, an estimated 500 million people are afflicted with malaria worldwide, killing more than one million people, most of whom are children in sub-Saharan Africa. The current malaria eradication program requires novel vector control methods to reduce the transmission of Plasmodium, the causative agent of malaria. These new methods must: target exophagic and exophilic Plasmodium vectors, integrate with current vector control efforts, be evaluated in the field in combination with other interventions, evade potential behavioral mechanisms that mosquitoes may evolve to avoid the intervention, new agents should have different modes of action, reduce the risk of physiological resistance development, and affect vector population age structure. This dissertation addresses how ivermectin mass drug administration, meets and exceeds all of these issues. Laboratory-based experiments demonstrated that ivermectin at human relevant pharmacokinetics affects Anopheles gambiae s.s. survivorship and that cumulative ivermectin blood meals compound mortality, blood feeding frequency, knockdown, and recovery. Field-based experiments demonstrate that ivermectin mass drug administration to humans reduces the survivorship of wild-caught Anopheles gambiae s.s. and probably Anopheles arabiensis up to six days post-administration. Most importantly, ivermectin mass drug administration to humans was shown to reduce the proportion of field-caught Plasmodium falciparum-infectious Anopheles gambiae s.s. for at least 12 days post-treatment. Ivermectin mass drug administration could be a powerful addition to malaria eradication campaign efforts.
Keywords: malaria; ivermectin; control; Plasmodium; Anopheles gambiae